N-acetylcysteine and fructose-1,6-bisphosphate: immunomodulatory effects on mononuclear cell culture N-acetilcisteína e frutose-1,6-bisfosfato: efeito imunomodulador em cultura de células mononucleares - Ricardo Obalski de Mello; Adroaldo Lunardelli; Eduardo Caberlon; Cristina Machado Bragança de Moraes; Roberto Christ Vianna Santos; Vinícius Lorini da Costa; Gabriela Viegas da Silva; Patrícia da Silva Scherer; Luiz Eduardo Coimbra Buaes; Márcio Vinícius Fagundes Donadio; Fernanda Bordignon Nunes; Jarbas Rodrigues de Oliveira (Sociedade Brasileira de Patologia Clínica, 2012)
INTRODUCTION: Sepsis is a complex syndrome caused by an uncontrolled systemic inflammatory response. Inflammatory cytokines play a pivotal role in septic shock pathogenesis. Therapeutic strategies have been tested in order to modulate the excessive generation or function of sepsis mediators. OBJECTIVE: The objective of the present study was to investigate the therapeutic effect of N-acetylcysteine (NAC) and its association with fructose-1,6-bisphosphate (FBP) on T-lymphocytes proliferation, interleukin-1β (IL-1β) and monocyte chemotactic protein-1 (MCP-1) levels. MATERIAL AND METHODS: Peripheral blood mononuclear cell samples were isolated from healthy individuals. T-lymphocytes were stimulated with phytohemagglutinin for 96 hours and submitted to different concentrations of NAC or NAC associated with FBP. RESULTS: NAC (10 and 15 mM) and NAC (15 mM) associated with FBP reduced T-lymphocytes proliferation. IL-1β levels rose in the presence of both NAC (15 mM) and NAC with FBP (1.25 mM). MCP-1 levels were reduced only by NAC (15 mM) associated with FBP (1.25 mM). CONCLUSION: The results suggest that both NAC itself and NAC associated with FBP inhibit cellular proliferation, acting as potent immunomodulatory agents, which corroborates its use in the treatment of inflammatory diseases. INTRODUÇÃO: A sepse é uma síndrome complexa causada pela resposta inflamatória sistêmica descontrolada. As citocinas inflamatórias representam papel central na patogênese do choque séptico. Têm sido testadas estratégias terapêuticas a fim de modular a geração ou a função excessiva de mediadores na sepse. OBJETIVO: O objetivo deste estudo foi investigar o efeito terapêutico da N-acetilcisteína (NAC) e sua associação com a frutose-1,6-bisfosfato (FBP) sobre a proliferação de linfócitos T e a geração de interleucina-1β (IL-1β) e proteína quimiotática de monócitos 1 (MCP-1) em cultura celular. MATERIAL E MÉTODOS: Foram isoladas células mononucleares de sangue periférico de indivíduos saudáveis. Os linfócitos T foram estimulados por 96 horas com fitohemaglutinina e submetidos a diferentes concentrações de NAC ou NAC associada à FBP (1,25 mM). RESULTADOS: O tratamento com NAC (10 e 15 mM) ou NAC (15 mM) associado à FBP reduziu a proliferação celular. Os níveis de IL-1β aumentaram com a presença de NAC (15 mM) e NAC + FBP. A concentração de MCP-1 mostrou-se reduzida apenas no grupo tratado com NAC associada à FBP. CONCLUSÃO: Os resultados sugerem que tanto a NAC quanto a NAC associada à FBP são capazes de inibir a proliferação celular, atuando como potentes agentes imunomoduladores, sugerindo seu uso em doenças inflamatórias.